Penerapan Metode Belajar Asik dalam Meningkatkan Literasi dan Numerasi Siswa/I Melalui Program Kampus Mengajar di Sekolah Dasar Negeri 064988 Medan Johor - Ester Sitindaon; Tuti Atika (Yayasan Literasi Sains Indonesia, 2023)
Literacy and numeracy are the basic skills students need to analyze readings or numbers in different contexts. Based on the research results, it is known that Indonesian students' reading and mathematics skills are still lacking. Therefore, under the Merdeka Learn Kampus Merdeka (MBKM) policy, the Ministry of Education and Culture organizes the Education Campus Program which invites students to participate in strengthening students' literacy and numeracy skills, especially at the elementary school level. Students directly help the school, teachers and students, depending on the condition of the school and existing needs. With this teaching campus program, I directly teach literacy and numeracy to students using cool learning methods. a method that can attract interest and motivate students to be more active in carrying out the learning process which takes place at public elementary school 064988 Medan Johor. At the beginning of using this cool learning method, students seemed to enjoy the teaching and learning process more. At the beginning of using this learning method, I myself did not experience any difficulties. Due to the good reception of students towards this learning method.